2009
DOI: 10.5194/hessd-6-3199-2009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative predictions of discharge from an artificial catchment (Chicken Creek) using sparse data

Abstract: Abstract. We used ten conceptually different models to predict discharge from the artificial Chicken Creek catchment in North-East Germany. Soil textural and topography data were given to the modellers, but discharge data were withheld. We compare the predictions with the measurements from the 6 ha catchment and discuss the conceptualization and parameterization of the models. The predictions vary in a wide range, e.g. the predicted actual evapotranspiration ranged from 88 to 579 mm/y and the discharge from 19… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 47 publications
0
30
0
Order By: Relevance
“…Even, sandbank island sediments consisting of quartz sand had lower K s values (2.4-3.8 m day − 1 ) Klaassen et al, 2008) than observed in the present study. Moreover, the observed K s was even much higher than that of other artificial ecosystems such as engineered covers (8.6 × 10 − 7 -8.6 × 10 − 1 m day − 1 ) (Bohnhoff et al, 2009;Ogorzalek et al, 2008) and the artificial Chicken Creek catchment (0.2-2.3 m day − 1 ) (Gerwin et al, 2009;Holländer et al, 2009;Mazur et al, 2011). However, most of these studies (e.g.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…Even, sandbank island sediments consisting of quartz sand had lower K s values (2.4-3.8 m day − 1 ) Klaassen et al, 2008) than observed in the present study. Moreover, the observed K s was even much higher than that of other artificial ecosystems such as engineered covers (8.6 × 10 − 7 -8.6 × 10 − 1 m day − 1 ) (Bohnhoff et al, 2009;Ogorzalek et al, 2008) and the artificial Chicken Creek catchment (0.2-2.3 m day − 1 ) (Gerwin et al, 2009;Holländer et al, 2009;Mazur et al, 2011). However, most of these studies (e.g.…”
Section: Discussionmentioning
confidence: 69%
“…Discrepancies between measured and predicted K s values have been reported on both natural soils (e.g. Sobieraj et al, 2001;Tietje and Hennings, 1996), artificial ecosystems (Holländer et al, 2009) and well-sorted marine sands (Wilson et al, 2008). The poor performance of the PTFs observed in the present study may be due to a number of reasons; first, the PTFs were developed based on databases for natural soils, most of which tend to be poorly sorted.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations